AKIBAT HUKUM PUTUSAN PEMBUBARAN PARTAI POLITIK DAN EKSKLUSIVITAS HAK PEMOHON OLEH MAHKAMAH KONSTITUSI TERHADAP PUTUSAN MK NOMOR 53/PUU-IX/2011 - Pardamean Harahap; Mochamad Yulian Fadhli Saputra; Muhamad Noval Faris Pratama; Ahmad Jafar Sidik; Galuh Candra Utami; Talitha Kamilah; Claraditha Adelia Nelson; Zahra Ramadhanty Drajat; Asyifa Nayla Jingga (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The dissolution of political parties is one of the Constitutional Court’s authorities to safeguard democracy, state ideology, and the integrity of the Republic of Indonesia. Constitutional Court Decision Number 53/PUU-IX/2011 affirms that the Government is the only party with legal standing to petition for the dissolution of a political party. This study aims to analyze the juridical implications of such exclusivity and the legal consequences arising from a dissolution decision. This research employs a normative legal method through statutory, case, and literature approaches. The results show that limiting legal standing is intended to maintain national stability, but it also restricts citizens’ participation in monitoring political parties. Furthermore, the dissolution of a political party results in the revocation of its legal entity status, termination of its activities, state acquisition of its assets, and restrictions on certain political rights of its officials. Therefore, strengthening legal mechanisms is necessary to ensure legal certainty and uphold constitutional democracy.